The role of gender in improving adaptation to climate change among small-scale fishers. (18th August 2018) - Musinguzi, Laban; Natugonza, Vianny; Efitre, Jackson; Ogutu-Ohwayo, Richard
Abstract : Climate change disproportionately affects marginalized groups, especially women. To guide the integration of gender roles in interventions to improve adaptation, we examined gender roles among fishers on Lake Wamala, Uganda, which has been increasingly affected by climate change. We found lower participation of women than men in preharvest and postharvest fishing activities, with 99% of fishers and 92.9% of fish processors and traders combined being men. The men had more fishing experience, started fishing at a younger age and exited at a later age, targeted more species, used more fishing gears and bought more fish for processing and trading. Although we observed diversification to non-fishery livelihoods, such as crop and livestock production to increase food security and income among others, income from these activities was not controlled or shared equally between men and women. Compared to men, women worked longer hours, engaging in more simultaneous activities both in and out of the home and reported less time resting. The income controlled by women was used directly to meet household needs. The implications of these differences for adaptation, what men and women can do best to enhance adaptation and how some adaptation practices and interventions can be implemented to benefit both men and women are discussed.